Nanocarbon based field effect transistors for biosensing applications - Herry Gunadi Sudibya (2011)
Nanocarbon materials, including Single Walled Carbon Nanotubes (SWNTs) and graphene, with their unique combination of electrical, physiochemical, and structural properties, has recently emerged as a novel nanoelectronic biosensor for chemical and biomolecular detection. Their major advantages; including the simple detection scheme, high sensitivity and selectivity, and capability to show real time monitoring; make those materials to receive increasing attention in the last few years. In the synthesis process of carbon nanotubes (CNTs), the product obtained is always mixture of metallic and semiconducting; an electrical property which is determined by their chiralities. Effective separation technique, which mainly aims for high purity semiconducting tubes, should be achieved to develop high-quality sensor. Among various techniques for chirality characterization, our results demonstrate that the electrical transport measurement (through Ion/Ioff ratio) of thin film Field Effect Transistors (FETs) is the most sensitive technique; compare to photoluminescence excitation spectroscopy, optical absorption spectroscopy, or Raman spectroscopy; in order to evaluate the purity of semiconducting CNTs.